Effects of Nano Silica and Silica Fume on Compressive and Tensile Strength of Concrete (International Journal of Innovative Research in Engineering & Management, 2023)
The application of nanotechnology in  concrete adds new content to efforts to improve its  performance. Due to the very small size of nano materials,  the properties of concrete can be influenced by changing  the microstructure. The study involved the use of Silica  fume (3%,6%,9%) and nano-silica (1%,2%,3%) b.w.c. As  the percentage of Silica fume and nano silica increases, an  increase in strength is observed.  Concrete is the material of present and future, It’s widespread use in structures, from buildings to factories,  bridges and airports, makes it one of the most searched material. Due to rapid population explosion and the rise of  technology to meet these needs, there is an urgent need to  improve the strength and durability concrete. Among the  various materials used in concrete production, cement  plays an important role due to its size and adhesive  properties. Therefore, for the production of improved concrete, the cement humidification mechanism should be studied properly and better alternatives should be  proposed. In this study, the cement is replaced by silica fume and nano silica materials. In addition, it is planned  to determine the number of predictions of cubes in the program. These theses explore the standard optimization  ratio for silica and fume to get the best compressive  strength. Further this has to check for Indian standard uses  for developing the demand of quality users in India.  All of the concrete mixtures were tested. These tests  include performing Slump, compressive strength test. 24  cubes were molded for compressive strength, curing ages  of 7,28 days for the concrete mixtures were applied in this  work. The results proved the increase in compressive  strength, durability, and various other properties of  concrete by adding nano silica and silica fume in concrete.
Keywords: Concrete; M40; M30; Silica Fume; Nano Silica